Does capital tax uncertainty delay irreversible risky investment? - Rainer Niemann; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2016)
Tax uncertainty is often claimed to be harmful for investments. Capital taxes, such as property and wealth taxes, are particularly exposed to tax uncertainty. Capital tax uncertainty emerges from expected tax reforms, the unclear outcome of future tax audits, and simplified estimates of capital tax bases in investment models. Uncertain returns on investment as well as stochastic taxation contribute to overall uncertainty and may significantly affect investment decisions. Hitherto, it is unknown how capital tax uncertainty affects investment timing. However, it is well known that both uncertainty and capital tax may be harmful for investment and decelerate investment activities. We are the first to study the investment timing effects of stochastic capital taxes in a real options setting with risky investment opportunities. Our results indicate that even risk neutral investors are sensitive with respect to capital tax risk and may react in a surprising manner to a newly introduced stochastic capital tax. As an apparently paradoxical investment effect, we find that increased capital tax uncertainty can accelerate risky investment if such uncertainty is sufficiently low compared to cash .ow uncertainty. In contrast, high capital tax risk delays high-risk innovative investment projects. To reduce unintended consequences of uncertain tax policy, tax legislators and tax authorities should avoid high levels of capital tax uncertainty. Broadening the capital tax base or increasing the capital tax rate induces ambiguous timing effects. Furthermore, high-growth investments are likely to be postponed if they experience a capital tax cut. Since investment reactions upon tax reforms are well-known to affect income and wealth distribution, reliable estimations of the impact of taxes on economic decisions are necessary.
Keywords: H25; H21; 330; property tax; capital tax; investment decisions; real options; timing flexibility; uncertainty